Empirical likelihood confidence intervals for the mean of a long-range dependent process - Daniel Nordman; Philipp Sibbertsen; Soumendra N. Lahiri (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
This paper considers blockwise empirical likelihood for real-valued linear time processes which may exhibit either short- or long-range dependence. Empirical likelihood approaches intended for weakly dependent time series can fail in the presence of strong dependence. However, a modified blockwise method is proposed for confidence interval estimation of the process mean, which is valid for various dependence structures including long-range dependence. The finite-sample performance of the method is evaluated through a simulation study and compared to other confidence interval procedures involving subsampling or normal approximations.
Keywords: C22; C13; 330; blocking; confidence interval; empirical likelihood; FARIMA; long-range dependence